Canine thyroid hemangiosarcoma: Case report - Salinas C., Eben (2024)
A thyroid hemangiosarcoma is reported in a 4-year-old canine patient. In the clinical evaluation it was identified a large volume mass located in the ventral region of the neck. Ultrasound study of the thyroid was the best technique to identify and describe neoplastic changes, as well as a metastatic lesion to an adjacent lymph node. In the surgical approach, the neoplasia presented marked infiltration to soft and vascular structures, being classified as a non-resectable tumour.